Nilai Kearifan Lokal dan Strata Sosial Tradisi Perayaan Maulid Nabi Muhammad SAW di Desa Kemuja, Kabupaten Bangka - Muhammad Rozani; Alim Bahri (Universitas Djuanda Bogor, 2023)
Mawlid Nabi is the anniversary of the birth of the Prophet Muhammad SAW which is held every 12 Rabi'ul Awal. By some people, the birthday of the prophet is commemorated as a review of the memory of the birth as well as the struggle of the Prophet Muhammad in spreading the da'wah of Islam throughout his life. There are many ways that people do in commemorating the birthday of the prophet and each region has its own way. The Kemuja village community is one of them. The celebration of the Birthday of the Prophet Muhammad SAW in the village of Kemuja embeds various series of activities with Islamic nuances, such as cultural festivals, barzanji readings, nganggung, and closed with a gathering to eat together. The purpose of this study is to describe the values ​​of local wisdom contained in the implementation of the tradition of celebrating the birthday of the Prophet Muhammad SAW in the village of Kemuja. The method used in this research is qualitative method. The techniques used in obtaining this data are observation, interviews, and literature study. Data analysis used descriptive qualitative by describing, analyzing, interpreting, and drawing conclusions. The results of the study found the values ​​of local wisdom and social strata inherent in the tradition of celebrating the birthday of the Prophet Muhammad in Kemuja village. The value of wisdom for peace and the value of wisdom for prosperity. Social strata are not a problem for most Kemuja villagers regarding the implementation of the prophet's birthday celebration. This is evidenced by the implementation of celebrations that take place lively, lively, and magnificently from year to year, so that this can be transformed as empowerment to form a fortress of prosperity and peace in society. Keywords: The value of local wisdom, social strata, traditions, the Prophet's mawlid.